2014
DOI: 10.3201/eid2004.131685
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of US Porcine Epidemic Diarrhea Virus Strain PC21A in Gnotobiotic Pigs

Abstract: To understand the progression of porcine epidemic diarrhea virus infection, we inoculated gnotobiotic pigs with a newly emerged US strain, PC21A, of the virus. At 24–48 hours postinoculation, the pigs exhibited severe diarrhea and vomiting, fecal shedding, viremia, and severe atrophic enteritis. These findings confirm that strain PC21A is highly enteropathogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
245
3
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(277 citation statements)
references
References 15 publications
21
245
3
8
Order By: Relevance
“…19 PEDV replication in mature enterocytes is rapid, with previous investigations demonstrating antigen or detecting nucleic acid 24 hpi. 2,7,11 In the current study, PEDV antigen and RNA were detected at 12 hpi. It is possible that PEDV RNA detected by fecal swab collection at 12 hpi represented the inoculum as it passed through the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 PEDV replication in mature enterocytes is rapid, with previous investigations demonstrating antigen or detecting nucleic acid 24 hpi. 2,7,11 In the current study, PEDV antigen and RNA were detected at 12 hpi. It is possible that PEDV RNA detected by fecal swab collection at 12 hpi represented the inoculum as it passed through the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The finding could be a consequence of gut permeability in 1-day-old piglets; however, it was recently reported that PEDV viremia can occur in the acute stage of infection of young inoculated gnotobiotic pigs and naturally infected 3-to 5-month-old commercial swine, thus suggesting that the young age of piglets in this study was not the reason for the high prevalence of viremia. 7 Detection of PEDV RNA in nonenteric tissue samples has not been reported and may well be a function of viremia. Although the identification of PEDV in extraintestinal tissues suggests the potential for avenues of virus transmission other than the fecal-oral route, this has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, epidemic PEDV strains are highly enteropathogenic and mainly infect villous epithelial cells of the small intestine before disseminating (11,12). It is well known that the intestinal epithelium has two important functions: absorbing helpful substances and providing a physical fence against harmful substances.…”
mentioning
confidence: 99%
“…The extent of intestinal villi shortening was associated with the stage of the infection or disease process. 101 Massive loss of absorptive enterocytes by PEDV infection results in a consequence of malabsorption, followed by watery diarrhea and dehydration in piglets.…”
Section: Gross and Histological Lesionsmentioning
confidence: 99%
“…12,101 Histological lesions of PEDV infection include cytoplasmic vacuolation and exfoliation of small-intestinal enterocytes in superficial villous, necrosis of scattered enterocytes followed by sloughing, and contraction of the subjacent villous lamina propria containing apoptotic cells. The extent of intestinal villi shortening was associated with the stage of the infection or disease process.…”
Section: Gross and Histological Lesionsmentioning
confidence: 99%